Effect of the structure of ethylene-propylene-diene-graft-polystyrene graft copolymers on morphology and mechanical properties of SAN/EPDM blends (eXPRESS Polymer Letters, 2007)
Ethylene-propylene-diene-graft-polystyrene (EPDM-g-PS) copolymers were synthesized to obtain different structures of graft copolymers with different graft lengths and graft densities. The structure of synthesized EPDM-g-PS copolymers was characterized by gel permeation chromatography (GPC) and by Fourier transforms infrared spectroscopy (FTIR). These presynthesized graft copolymers were added (5 phr) to styrene-acrylonitrile (SAN) and ethylene-propylene-diene (EPDM) blends, prepared to maintain the following SAN/EPDM ratios a) 95/5 and b) 90/10. SAN/EPDM blends were characterized by the determination of mechanical properties (tensile strength, elongation at break) while their morphology was inspected by scanning electronic microscopy, SEM. The obtained results show that various structures of EPDM-g-PS copolymers influence the miscibility in SAN/EPDM blends. Optimal concentration of side branches of graft copolymers provide the finest morphology and enhance mechanical properties.